Petrified auricular cartilages pointing the diagnosis of post-partum hypopituitarism in an encephalopathic patient - Machado, A (2009)
True ossification of ear auricles is exceptional. We present the first case linking this finding to post-partum hypopituitarism. A 57-year-old female presented with a 2-day history of fever, headache and behavioural disturbances. Brain magnetic resonance imaging was normal. Since cerebral spinal fluid could not be obtained, she was treated empirically for a meningitis. A urinary tract infection was subsequently identified as the cause of fever but when she improved she remained apathetic. At this time petrified auricles were noticed; histological examination revealed true ossification. Endocrinological screening showed partial hypopituitarism and thyroid autoimmune disorder. Initial symptoms could be dated to the birth of her last child 15 years before, with breast feeding difficulties, loss of body hair, and transient amenorrhoea. The absence of overt peripartum bleeding, resumption of menses 1 year later, preservation or recovery of some hypophyseal function, and presence of an associated autoimmune thyroid disorder and of hypophyseal tissue in a normal sella turca, all suggest lymphocytic hypophysitis rather than Sheehan syndrome as the primary disorder. Of the 15 patients reported to date with auricular ossification, two had Addison disease. The present case suggests that low cortisol is the key factor in this clinical finding.